Feasibility and integration of a novel bubble CPAP system into a public referral PICU in Mysuru, India - Rudman, Molly K.; Badin, Sarah; Ramaraj, Savitha M.; Rangaswamy, Shalini S.; Rauschendorf, Paula K.; Prakash, Raj; Boisson-Walsh, Alix; Burke, Thomas F. (Frontiers in Pediatrics, 2026)
ObjectiveThe objective of this study was to evaluate the feasibility of use and integration of a novel bubble CPAP (bCPAP) system into the PICU of the Mysore Medical College and Research Institute, India.Study designWe conducted an explanatory sequential prospective mixed-methods study using questionnaire-based surveys, focus group discussions (FGDs), and patient records. Survey and FGD participants included nurses, pediatric postgraduates, and pediatricians who worked in the PICU and used the bCPAP system. The FGDs were transcribed, coded, and systematically analyzed for emergent themes using the COM-B framework.ResultsFrom July 31, 2023, to July 24, 2024, 81 children were treated with the bCPAP system. The median age was 6.5 months (IQR: 3–11), the median weight was 6.5 kg (IQR: 4.9–7.8), and the median treatment duration was 24 h (IQR: 18–38). Most (n = 72, 89%) patients treated with the bCPAP system were discharged home. Forty-eight healthcare workers completed the survey, and 29 participated in the FGDs. Survey respondents rated the bCPAP system as more effective (67%) or much more effective (17%) than previous treatments for respiratory distress. They found the integration of the bCPAP system into the PICU feasible (63%) or very feasible (35%). FGD participants reported that the bCPAP system was easy to use, portable, and required minimal training. They also noted rapid patient improvement and a reduction in the number of patients requiring mechanical ventilation.ConclusionThe bCPAP system was integrated and adopted into the PICU of this public referral facility in Mysuru, India. Further research is needed in additional settings.